Qualifications frameworks and learning outcomes : challenges for Europe's lifelong learning area - Bohlinger, Sandra [Verfasser] (My University, 2012)
"Qualifications frameworks are political instruments that are supposed to facilitate the assessment of learning outcomes. They are hoped to be drivers for change since they are meant to provide the impetus for a number of fundamental reforms required in education and training systems. These considerations frame the design and implementation of coherent reforms, strategies and instruments. Thus, there are conceptual, political and procedural issues which are equally worthy of attention. Focusing on the European area, this paper addresses the question of whether the development of qualifications frameworks yields the anticipated benefits of the 'shift to learning outcomes'. The aim of the contribution is to review previous experience with learning outcomes and its links with qualifications frameworks as well as to analyse the current trends and challenges within the European countries." (Autorenreferat, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; S 2.3 Berufsbildungspolitik; I 2.2 Europa; Lernergebnisorientierung; Qualifikationsrahmen; Berufsbildungspolitik; Europa